PREVALENCE OF DYSLIPIDEMIA EUTROPHIC ADOLESCENTS (Fiep Bulletin - online, 2014)
To verify the dyslipidemias prevalence in eutrophic adolescents. Methodology: The sample was constituted of 49 males 63 females, with ages between 13 and 16 years, classified in the 3 and 4 sexual maturation stages (TANNER, 1962). From the relationship corporal mass / height2 was calculated the IMC to classify the nutritional status, establishing as eutrophia cut point the percentil 85th. For the determination of the blood concentrations of the total cholesterol, HDL-C and triglycerides (TG) the enzymatic-colorimeter method was used. LDL-C was calculated by the Friedewald et al. (1972) formula: LDL-C = CT - HDL-TG/5. The descriptive statistics was used (mean and standard deviation), soon after distribution of frequencies was accomplished for classification of the lipidic profile. Results: Hipercholesterolemia were detected in 12,3% of the boys and 25,4% of the girls presenting limits values, and 20,4% of the boys and 12,7 of the girls with elevated values. The LDL-C increased was found in 20,4% of the boys and 22,2% of the girls presenting limits values, and 6,1% of the boys with elevated values. They presented bordering values of the boys' HDL-C 59,2% and 49,2% of the girls. The hipertriglyceridemia was found in 8,1% of the boys and 14,3 of the girls with limits values, and 8,2% of the boys and 14,3% of the girls with elevated values. Conclusion: These results take to the need of adopting an efficient strategy of nutritional orientation and incentive to the practice of physical activities, in the intention of to revert or to maintain the blood lipids concentrations in this adolescents.
Keywords: dyslipidemia; risk factors; adolescents